Comparison of electroless Ni-P/ Ni-B on corrosion performance - John Leon, S; T. WinowlinJappes, J; Edwin Sahayaraj, M (International Journal of Engineering and Technology, 2018)
This research work compares annealed and as-coated electroless Ni-P’s resistance to corrosion and electroless Ni-B coating prepared on the mild steel substrate. The coatings’ resistance to corrosion was estimated by Tafel electro chemical polarization method utilizing electrochemical analyser in 3.5wt % solution of Sodium Chloride. Both the coatings’ annealing temperatures were maintained at normal intervals to consider their corrosion resistance performance. Further, the corrosion behaviour of both the coatings with their as-coated and various annealed temperature were discussed for the deliberation of deposits phases, crystallite sizes and micro strain.